“A very small cog in the wheel”: principals’ perceptions of change and continuity in the wake of ESSA reforms - Kim, Jihyun; Reid, David B.; Galey, Sarah (Asia Pacific education review, 2024)
In 2015, the Every Student Succeeds Act (ESSA) was signed into law, replacing No Child Left Behind as the statutory education policy of the federal government of the United States (US). Building on prior shifts in accountability policy at the state level, ESSA focused attention and resources on building school leadership capacities. Five years on, how has the implementation of ESSA changed principals’ perceptions of accountability? We compare state policy documents and principal interviews to elucidate the impacts of ESSA on school accountability and leadership in two states—Pennsylvania and New Jersey. Despite major differences in state support for principal’s capacity building found in ESSA plans, interview data suggest that most principals have little knowledge of ESSA policy and do not perceive the influence of ESSA on changes in their day-to-day work. We discuss the implications of this discrepancy between the ESSA policy and practice for researchers and school leaders.